2020
DOI: 10.1089/heq.2020.0057
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Limited English Proficiency and Access to Health Insurance and Health Care in the Affordable Care Act Era

Abstract: Purpose: Limited English proficiency adversely impacts people's ability to access health services. This study examines the association between English language proficiency and insurance access and use of a usual care provider after the implementation of the Affordable Care Act (ACA). Methods: Using cross-sectional data from the 2016 Medical Panel Expenditures Survey, we identified 24,099 adults (weighted n =240,035,048) and categorized them by self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Informational resources for individuals with limited English-speaking ability may be less accessible due to a lower likelihood of health insurance and access to a usual care provider (Foiles Sifuentes et al, 2020) and explain the significantly lower odds of genetic testing awareness among non-White respondents with low English proficiency as underrepresented racial and ethnic groups have been found to have lower access to health coverage (Cohen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Informational resources for individuals with limited English-speaking ability may be less accessible due to a lower likelihood of health insurance and access to a usual care provider (Foiles Sifuentes et al, 2020) and explain the significantly lower odds of genetic testing awareness among non-White respondents with low English proficiency as underrepresented racial and ethnic groups have been found to have lower access to health coverage (Cohen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Latinx populations may be at particular risk of SARS-CoV-2 because of overrepresentation in essential jobs requiring face-to-face interactions, reliance on public transportation, and multi-generational living [ 4 ]. Healthcare access among Latinx LEP communities can be additionally limited by socio-political barriers [ 4 ]; Latinx patients with LEP are more likely to be underinsured than non-Spanish-speaking patients with LEP [ 5 ]. Although data on outcome variation by LEP status is scarce, there is some evidence that Latinx patients with LEP may be at higher risk for poor health than patients with LEP of different racial/ethnic backgrounds [ 6 ].…”
Section: To the Editormentioning
confidence: 99%
“…Compounding this challenge was the high proportion of COFA households (52.3%) reporting challenges with accessing services due to LEP 29. Other US contexts have demonstrated that those with LEP are much less likely to be insured than other populations, both because of related socioeconomic barriers and the direct impact of difficulty understanding printed materials and communication with insurance providers 5 30…”
Section: Mechanism 1: Complex Communication Challengesmentioning
confidence: 99%
“…In the USA, the high costs of care coupled with a large proportion of uninsured individuals contributes to substantial annual risks of catastrophic health expenditures 4. Low-income individuals, migrants and those with limited English proficiency (LEP) are at particular risk 5 6…”
Section: Introductionmentioning
confidence: 99%